POLA PRODUKSI AJMALISIN DARIKULTUR AGREGAT SEL Catharanthus roseus (L) G Don. DALAM BIOREAKTOR - Aida Muspiah; Rizkita Rahmi Esyanti; Arbayah H Siregar; Erman Tritama (Research Center for Biology-Indonesian Institute of Sciences, 2002)
A research has been conducted to optimize the rate of aeration and initial cell aggregates weight in the production of ajmalicine in Catharanthus roseus cell culture in bioreactor. Catharanthus roseus culture were grown in Zenk medium with the addition of 2.5 x 10